Sartorial Objects, Transgender Bodies and Destabilized Meaning: A Study of Kaushik Ganguly’s Nagarkirtan - Nizam, Hamalna (Spectrum, 2022)
Kaushik Ganguly’s 2017 film Nagarkirtan narrates the story of Puti, a transgender belonging to a hijra group in Kolkata, who desires for a gender reconfirmation surgery. Puti’s sartorial choices help her construct or emulate the appearance of a body she longs for but cannot avail due to her poor financial condition. On one hand, her sartorial choices help her to express her felt gender; on the other hand, it betrays her by either limiting her identity or giving out misinformation about the body that lies beneath. The paper uses Butler’s idea of impermanence of meaning behind signs and Halberstam’s idea of ‘trans’ being a destabilizing element of societal norms to present a qualitative analysis of the trans protagonist’s social performances through sartorial preferences as depicted in Nagarkirtan. Since the film under discussion shows its transgender protagonist at various stages of life, the paper also discusses her clothing choices throughout the years to explore the complex relationship among the clothes, the trans body and societal expectations. Spectrum, Volume 16, June 2021: 195-206